High-temperature radiation resistance of NiCoFe medium-entropy alloy enabled by stable nanostructures and defect evolution mechanisms - Nori, Sri Tapaswi; Esfandiarpour, Amin; Kalita, Damian; Zieliński, Maciej; Mulewska, Katarzyna; Bjørge, Ruben; Vullum, Per Erik; Ferreirós, Pedro A.; Chrominski, Witold; Li, Mingyang; Chang, Yongqin; Zhang, Yanwen; et al. (Journal of materials research and technology, 2025)
The study innovatively examined a nano oxide dispersion-strengthened (ODS) NiCoFe medium-entropy alloy with nanosized grains to address the challenge of discovering structural materials for high-temperature irradiation applications, such as in advanced nuclear reactors. The ODS-NiCoFe alloy exhibited a nanoindentation hardness of 4.3 ± 0.9 GPa, representing a two-fold enhancement over the 2.0 ± 0.1 GPa of single-crystal NiCoFe. Dislocations were identified as the primary defect structures. Following irradiation (Ni2+, 580 °C), the average dislocation length density increased from ∼2.6 × 1013 m−2 to ∼6.1 × 1013 m−2, while the mean dislocation length decreased from 249 nm to 104 nm, contributing to a relative irradiation hardening of 25 %. Additionally, the study demonstrated the stability of various nanostructures, with only minor changes in the average sizes of nanoprecipitates and grains—from 6.7 ± 1.7 nm to 6.4 ± 1.7 nm, and from 73 ± 2 nm to 76 ± 2 nm, respectively, upon irradiation, suggesting effective defect annihilation at interfaces and grain boundaries. The alloy exhibited no observable irradiation-induced voids. Molecular dynamics simulations revealed irradiation resistance of the alloy through the absorption of vacancy clusters at grain boundaries and Shockley-dominant-dislocation chains and the absorption of interstitial clusters at grain boundaries, aided by the high mobility and three-dimensional motion of interstitial clusters. Thus, the findings demonstrate the high-temperature radiation resistance of the novel ODS-NiCoFe alloy, surpassing that of well-known ODS steels, using a correlative approach that combines experiments and simulations.